Effect of Direct Fed Microbials (DFM) and Solid State Fermented (SSF) Biomass on Nutrients Digestibility and Rumen Fermentation in Surti Buffaloes - Mathukiya, Gaurang P; Pandya, Paresh R; Rathod, Sunil V; Sarvaiya, Nitesh P; Sorathiya, Kalpesh K (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Present study was carried out to evaluate the effect of supplementing Direct Fed Microbials (DFM) and Solid State Fermented (SSF) biomass for 70 days on body weight, nutrient intake, digestibility and rumen fermentation in adult Surti buffaloes (n=15). The animals were randomly allotted into three groups, with 5 animals in each group. The animals in the control group (T1) were fed TMR (Roughage to concentrate ratio of 65:35) without supplement, while the animals in group T2 and T3 were fed TMR with 3% DFM and 3% SSF biomass on DM basis, respectively. The average initial and final body weight (kg) of animals in T1 (411.8 and 428.8), T2 (412.2 and 433.1), and T3 groups (415.8 and 438.7, respectively) were more or less similar. None of the probiotics had significant effect on average DMI and CPI. The average daily DCPI was however significantly (p<0.05) higher in T3 and T2 than T1. Average bi-weekly total digestible nutrient intake was significantly (p<0.05) higher in T3 followed by T2 and T1 group. Digestibility of all nutrients was improved numerically by supplementation of DFM and SSF biomass in the diet of buffaloes, and was within the normal range. There was significantly (p<0.05) higher concentration of ammonia-N and TCA precipitable nitrogen in SRL of treatment groups of animals, while the values of SRL pH, TVFA, total-N, soluble-N and NPN were statistically similar between groups. The overall results suggested that supplementation of SSF biomass or DFM @ 3% in the ration of buffalo has no adverse effect on feed intake, digestibility and rumen fermentation. Further research is needed to explore their utilization in livestock ration.